Detectability of pulse distortion in an acoustic loudspeaker field - HOJAN, Edward (Archives of Acoustics, 1977)
This paper presents results of the evaluation of the distortion of transient signals produced by a set of loudspeakers. They were obtained on the basis of certain objective signal parameters and subjective tests. The separate objective parameters provided complex information on the degree of signal distortion and were correlated with the psychoacoustic ability of the sense of hearing to detect distortions. These parameters were related to the rising transients with complex spectra and to the decay transients with simple spectra.